Evaluation of Various Silicon- and Boron-Containing Compounds for the Detection of Phosphorylation in Peptides via Gas-Phase Ion-Molecule Reactions. Issue 4 (August 2014) - Piatkivskyi, Andrii; Pyatkivskyy, Yuriy; Ryzhov, Victor
Gas-phase ion–molecule reactions (IMR) of various boron- and silicon-containing neutrals were investigated as a potential route for detecting phosphorylation within peptides in the negative ion mode. Trimethyl borate (TMB), triethyl borate (TEB) and N, O -Bis(trimethylsilyl)acetamide (TMSA), unlike diethylmethoxyborane (DEMB), diisopropoxymethylborane (DiPMB) and chlorotrimethylsilane (TMSCl), reacted differently if a phosphate moiety was present and thus are suitable to detect phosphorylation. During multistage collision-induced dissociation experiments of the reaction products of IMR with TMB and TEB, the [LSsF − 4H + B] − ion formed a modified y2 * fragment allowing the phosphorylation site to be assigned, unlike reaction products of DEMB and DiPMB which lost both the phosphoric acid and the boron-containing moiety.